Reasons for an outstanding plant diversity in the tropical Andes of Southern Ecuador - Michael Richter; Karl-Heinz Diertl; Paul Emck; Thorsten Peters; Erwin Beck (Landscape Online, 2009)
Long-term field studies in the scope of a multidisciplinary project in southern Ecuador revealed extraordinary high species numbers of many organismic groups. This article discusses reasons for the outstanding vascular plant diversity using a hierarchical scale-oriented top-down approach (Grüninger 2005), from the global scale to the local microscale. The global scale explains general (paleo-) ecological factors valid for most parts of the humid tropics, addressing various hypotheses and theories, such as the "greater effective evolutionary time", constant input of "accidentals", the "seasonal variability hypothesis", the "intermediate disturbance hypothesis", and the impact of soil fertility. The macroscale focuses on the Andes in northwestern South America. The tropical Andes are characterised by many taxa of restricted range which is particularly true for the Amotape-Huancabamba region, i.e. the so called Andean Depression, which is effective as discrete phytogeographic transition as well as barrier zone. Interdigitation of northern and southern flora elements, habitat fragmentation, geological and landscape history, and a high speciation rate due to rapid genetic radiation of some taxa contribute to a high degree of diversification. The mesoscale deals with the special environmental features of the eastern mountain range, the Cordillera Real and surrounding areas in southern Ecuador. Various climatic characteristics, the orographic heterogeneity, the geologic and edaphic conditions as well as human impact are the most prominent factors augmenting plant species diversity. On microscale, prevailing regimes of disturbance and environmental stresses, the orographic basement, as well as the general role on the various mountain chains are considered. Here, micro-habitats e.g. niches for epiphytes, effects of micro-relief patterns, and successions after small-sized disturbance events are screened. Direct effects of human impact are addressed and a perspective of possible effects of climate change on plant diversity is presented.